Single dose versus multiple dose antibiotics in laparoscopic cholecystectomy: A prospective comparative single blind study - Koirala, Ashok; Thakur, Dipendra; Agrawal, Sunit; Chaudhary, Bhuwan Lal (Journal of Society of Anesthesiologists of Nepal, 2019)
Introduction: There is a controversy on single dose or multiple doses of prophylactic antibiotics for prevention of surgical site infection during laparoscopic cholecystectomy in a developing country setting. The objective of this study was to compare single versus multiple doses of prophylactic antibiotics in terms of surgical site infection in laparoscopic cholecystectomy patients. Methods: This was a prospective, comparative, randomized study was conducted in a medical college hospital. Two hundred consecutive patients with symptomatic cholelithiasis planned for routine laparoscopic cholecystectomy were enrolled in the study. Patients were randomly divided in a Single dose (SD) group and multiple dose (MD) group. SD group were given injection ceftriaxone (1gm) before induction of anesthesia and MD group received ceftriaxone (1gm) before induction of anesthesia and continued a total of 3 doses postoperatively for next 24 hours. Results: A total of 200 patients were studied, of which 100 were in single dose (SD group) and another 100 in multiple dose (MD group). The mean age of patients with symptomatic cholelithiasis was 41.76 ± 13.38 years with minimum of 16 years and maximum of 73 years. Of the total patients, 4 patients in single dose (SD) group and 3 patients in multiple dose (MD) group developed surgical site infection of various severity which was not statistically significant. (p=0.500). Conclusion: There is no difference in terms of surgical site infection in patients taking either single or multiple doses of antibiotics in laparoscopic cholecystectomy in a medical college setting in Nepal.